KONSEP PENDIDIKAN KARAKTER PEREMPUAN MINANGKABAU SEBAGAI IDE PENCIPTAAN LUKISAN EKSPRESI SIMBOLIK - Rest Melia Fenetri; Dharsono Dharsono; Ahmad Akmal (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2016)
ABSTRACT This study focuses on the concept of ideal woman according to Minangkabau philosophy. The criteria of the ideal woman can be found in proverbs containing implicit meaning related to ethical value namely the view about woman’s ideal morality. That interpretation can be comprehended from its function and purpose as a concept of moral and character education for Minangkabau young generation.The study toward the character education of Minangkabau woman based on the interpretation of meaning from the concept of Minangkabau ideal woman became the basis of fine art creative idea resulting on the icon of personal expression. This artwork was materialized into the painting of symbolic expression/abstraction by borrowing the traditional idiom “Tangkuluak (Tekuluk),” a kind of Bundo Kanduang’s formal outfit in the form of headgear as the traditional symbol Minangkabau custom.The creation of this symbolic expression painting aims at the preservation effort of Minangkabau aesthetics through the materialization of paintings that takes the specific theme, Bundo Kanduang as the ideal woman of Minangkabau people.This study used qualitative method presented in the form of descriptive analysis. The techniques of data collection conducted were interview and observation that had emic characteristic performed in the Centre of Minangkabau Cultural Information (in Indonesia, it’s called as PDIKM) in Padangpanjang and Adityawarman Museum in Padang, West Sumatra. While etic research was conducted with qualitative method namely studying the theoretical claim and interpreting the meaning of proverbs about the nobility of Bundo Kanduang.